ENTEROVIRAL IINFECTION IN NEWBORN - A. V. Bogdanov; O. V. Samodova; E. A. Krieger; A. V. Lobanov (Детские инфекции (Москва))
A case of generalized enteroviral infection of a newborn (encephalomyocarditis and dilated cardiomyopathy) was described. The 6 day old patient required close monitoring and intensive care because of severe heart failure. Diagnosis of enteroviral infection was made by detection of enterovirus RNA in the sterile body fluids — blood and cerebrospinal fluid.